PERAN PENYULUH PERIKANAN TERHADAP PENINGKATAN USAHA BUDIDAYA RUMPUT LAUT (Eucheuma sp) DI DESA PONDONG BARU KECAMATAN KUARO KABUPATEN PASER - Candra Aldi Zulikram; Nurul Ovia Oktawati; Eko Sugiharto (2339-1324, 2018)
The aim of research to study the role of fisheries extension to the enhancement and analyze revenue from seaweed farming in the village of Pondong Baru subdistrict Kuaro Paser. This research was conducted in February - March 2017 and the study site is in the village of Baru subdistrict Kuaro Pondong Paser. Scoring results showed an average extension being instrumental, with the value of the class interval 15,7. Extension perform his duties as supervisor of farmers, extension lower role, extension workers carry out their duties as Organizer and a dynamic role being. But the extension as technical supervisor and counselor as a bridge facilitator states the role of educator plays low. The results of the analysis of optimal reception address that was obtained during the production of seaweed with an average of 2,500 kg per 1 Harvesting (45 days), the maximum benefit is obtained with an average of Rp. 4,492,103, and the value of RCR 1.38.